2018
DOI: 10.1002/jcla.22408
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SLCO1B1 and APOE genetic polymorphisms in a large ethnic Hakka population in southern China

Abstract: We analyzed the SLCO1B1 and APOE gene polymorphisms in the Hakka population of southern China. This study provides a reference for the individualized meditation for Hakka population in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…We found significant differences in the frequency of haplotypes SLCO1B1 *1a(388A-521 T), *1b(388 G-521 T), *5(388A-521 C), *15(388 G-521 T): *1b/ *1b, *1b/*15, *1a/*1b, *1a/*15 and *1a/*1a are common, together accounting for 96.5% of our cohort. However, these data differ from those of Zhong et al [18], who found, for example, an *1b/*1b frequency of 40%, whereas in our population the frequency is 29%. The reasons for this are unclear but may reflect difference in recruitment in that their cohort is some five times larger than ours.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found significant differences in the frequency of haplotypes SLCO1B1 *1a(388A-521 T), *1b(388 G-521 T), *5(388A-521 C), *15(388 G-521 T): *1b/ *1b, *1b/*15, *1a/*1b, *1a/*15 and *1a/*1a are common, together accounting for 96.5% of our cohort. However, these data differ from those of Zhong et al [18], who found, for example, an *1b/*1b frequency of 40%, whereas in our population the frequency is 29%. The reasons for this are unclear but may reflect difference in recruitment in that their cohort is some five times larger than ours.…”
Section: Discussioncontrasting
confidence: 99%
“…Genotypes of SLCO1B1 influence adverse reactions with statins [18] [24,25]. Accordingly, we calculate that 2.7% of our cohort are at high risk for adverse statins reactions, a finding that promotes the view that those at highrisk need additional prevention and control guidance such as diet control and lifestyle improvement, and also regular health care screening, so enabling early diagnosis and targeted treatment.…”
Section: Discussionmentioning
confidence: 87%
“…The most common haplotype in the German (49.5%) and in the Turkish population (46.3%) was SLCO1B1 *1a 48 . Greek, 49 Roma and Hungarian, 50 Indian (North), 51 and Brazilian 52 populations exhibit relatively lower rates of *1b (<50%), whereas Thai 53,54 and Chinese 55 populations show higher rates, generally above 60%–70%. In contrast, the allele frequency of haplotypes *15 and *5 displayed little difference.…”
Section: Discussionmentioning
confidence: 99%
“…20 APOE is formed of two single nucleotide polymorphisms (SNPs): 388T > C (rs 429,358) and 526C > T (rs 7412), which can form three alleles, namely, ε2 (388T–526 T), ε3 (388T–526 C), and ε4 (388C–526 C). 12,21 There are two cysteine residues (cys) at sites 112 and 158 of the amino acid sequence for APOE ε2, while the cysteine residue is replaced by the positively charged arginine amino group (Arg) at site 158 in the amino acid sequence for APOE ε3, and is replaced by Arg at sites 112 and 158 for APOE ε4. 22 The difference among the three alleles lies in the change of two amino acids at sites 112 and 158, which makes the stability of the three alleles different, namely, ε4 < ε3 < ε2.…”
Section: Discussionmentioning
confidence: 99%